The Plant – Pathogen Interactions - CAHYA PRIHATNA (Microbiology Indonesia, 2009)
Interaction between plants and their pathogens is complex, involving multifaceted recognition of pathogens by the plants and, on the other hand, subtle evasion from the pathogens. Plants perceive pathogens through direct recognition of common molecular patterns in microbes and direct recognition of effectors or their perturbation on cellular components by the pathogens. Recognition of microbe- or pathogen-associated molecular patterns triggers innate immunity that renders plants resistant to most potential microbial pathogens. Recognition-dependant immunity in plants largely relies on polymorphism of resistance gene products that confer specificity towards host-specialised pathogens, which, in turn, induces more specific resistance that is effective against host-specialised pathogens. The deployment of effective resistance involves signalling of pathogen recognition through complex signalling cascades, transcriptional reprogramming, and defence-related genes, which all contribute to an arrest of pathogen growth. Our current insights into effector biology and to which the plants respond, provide a detailed information on the evolutionary arms race between plants and their pathogens. These will lead to an improvement of current strategies for crop improvement and protection.